Progress in Genetic Study of Breast Cancer: Brief Review - Salazar, Fabián (2023)
This review article examines the recent advances in genetic research on breast cancer and the emerging therapeutic strategies that are being investigated to improve the diagnosis and treatment of this disease. It discusses gene therapy techniques, the identification of genes related to breast cancer, and trends in genetic research such as personalized medicine and artificial intelligence. The advantages and disadvantages of each therapeutic approach, target goals, and utilization states are analyzed. A table summarizing the advances in genetic research on breast cancer is also presented, including techniques and trends for the development of new treatments, the current state of each technique and trend, preclinical and clinical treatments, and approved and marketed treatments. In conclusion, genetic research on breast cancer remains an evolving field, but advances in understanding the molecular mechanisms of the disease are driving the emergence of new therapeutic options, offering hope for improving the survival and quality of life of breast cancer patients.